Therapeutic exercises in the process of physical rehabilitation of athletes with traumatic injuries of the musculoskeletal system (based on futsal) - E. Yu. Doroshenko; S. M. Malakhova; O. Ye. Chernenko; A. M. Hurieieva; I. V. Shapovalova; I. O. Sazanova; M. O. Oliinyk; T. S. Svitlychna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of the work is to investigate and to test the effectiveness of therapeutic exercises in the process of physical rehabilitation of players in futsal after traumatic injuries of the musculoskeletal system.